Mathematical modelling problem solving with respect to students’ mathematical resilience in GeoGebra-assisted mea learning - Lutfiyana, Lina; Pujiastuti, Emi; Kharisudin, Iqbal (Fakultas Tarbiyah Universitas Ibrahimy, 2025)
Problem-solving is a crucial 21st-century skill that plays a vital role in mathematics education. One practical approach to developing this skill is through mathematical modelling, particularly by employing GeoGebra-assisted MEA learning. This study aims to: (1) evaluate the quality of GeoGebra-assisted MEA learning; (2) examine the influence of mathematical resilience on Mathematical Modelling Problem-Solving Ability (MMPSA); and (3) describe students’ MMPSA based on their levels of mathematical resilience. A mixed-methods approach was employed using a Sequential Explanatory design, with instruments including questionnaires, tests, observations, and interviews. The sample consisted of Class VII A as the experimental group and Class VII B as the control group, each comprising 30 students. Eight students were selected as qualitative subjects based on their mathematical resilience levels. The results indicate that GeoGebra-assisted MEA learning demonstrates high instructional quality and significantly enhances students’ MMPSA. Quantitative findings show that mathematical resilience has a significant effect, accounting for 30% of the variance in students’ problem-solving performance. These results are further supported by qualitative data obtained through observations and interviews. Students with high resilience tended to be confident, persistent, and effective in solving problems. Those with moderate resilience showed adequate capability but lacked precision, while students with low resilience were easily discouraged and exhibited low self-confidence. In conclusion, integrating quantitative and qualitative findings underscores the importance of fostering mathematical resilience to enhance students’ problem-solving abilities, particularly in the context of GeoGebra-assisted MEA in mathematical modelling.